Pendekatan Manajemen Modern Strategi Efektif untuk Meningkatkan Produktivitas Tim - Napitupulu, Rohani Lestari; Avian, Zakhi Bailatul Nur; Nugroho, Cahyo Adi; Pamuji, Slamet; Kasmin, Kasmin (Jayapangus Press, 2024)
This research discusses effective strategies for increasing team productivity through modern management approaches. In an increasingly complex and dynamic era, organizations are faced with the challenge of maximizing team performance to remain competitive. This research identifies various management methods that can be applied to create a more productive and collaborative work environment. Through case studies and literature analysis, we explore techniques such as open communication, efficient time management, and the application of digital technologies in team collaboration. The research results show that an inclusive and adaptive management approach contributes significantly to increasing team member motivation and engagement. Methods such as Agile and a results-based approach have been proven to significantly increase productivity and job satisfaction. By involving team members in the decision-making process and providing constructive feedback, organizations can build a positive and innovative work culture. This not only encourages creativity, but also creates a sense of belonging among employees. This research concludes that modern management strategies that focus on collaboration, effective communication and the use of technology can be the key to increasing team productivity. It is hoped that these findings can provide guidance for organizational leaders in formulating managerial policies that are more effective and responsive to team needs in the future. This research also invites further discussion about the importance of management adaptation in facing changing work dynamics and evolving challenges.